E-mail virus protection handbook - Syngress Media, Inc. (Rockland, Md. ; [Great Britain] : Syngress, 2000)
The E-mail Virus Protection Handbook is organised around specific e-mail clients, server environments, and anti-virus software. The first eight chapters is useful to both users and network professionals; later chapters deal with topics relevant mostly to professionals with an emphasis on how to use e-mail filtering software to monitor all incoming documents for malicious behaviour. In addition, the handbook shows how to scan content and counter email address forgery attacks. A chapter on mobile code applications, which use Java applets and Active X controls to infect email and, ultimately, other applications and whole systems is presented. The book covers spamming and spoofing: Spam is the practice of sending unsolicited email to users. One spam attack can bring down an entire enterprise email system by sending thousands of bogus messages or "mailbombing," which can overload servers. Email spoofing means that users receive messages that appear to have originated from one user, but in actuality were sent from another user. Email spoofing can be used to trick users into sending sensitive information, such as passwords or account numbers, back to the spoofer. * Highly topical! Recent events such as the LoveBug virus means the demand for security solutions has never been higher * Focuses on specific safeguards and solutions that are readily available to users.
Keywords: Electronic mail systems -- Security measures; Computer viruses; Electronic books